Multiplication of Polynoimals by Polynomials
Multiplying Binomial by a Trinomial
Ex 8.4, 1 (i)
Ex 8.4, 1 (ii)
Ex 8.4, 1 (iv)
Ex 8.4, 1 (iii) Important
Ex 8.4, 2 (i)
Ex 8.4, 2 (ii) Important
Example 8 (i)
Example 9 (i)
Ex 8.4, 2 (iii)
Ex 8.4, 2 (iv) Important
Ex 8.4, 1 (v) Important
Ex 8.4, 1 (vi) Important
Ex 8.4, 3 (iii) Important
Ex 8.4, 3 (i)
Ex 8.4, 3 (ii)
Ex 8.4, 3 (vi)
Ex 8.4, 3 (viii) You are here
Example 10
Ex 8.4, 3 (iv)
Ex 8.4, 3 (v) Important
Ex 8.4, 3 (vii) Important
Multiplication of Polynoimals by Polynomials
Last updated at April 16, 2024 by Teachoo
Ex 8.4, 3 Simplify. (viii) (𝑎+𝑏+𝑐)(𝑎+𝑏−𝑐) (𝑎+𝑏+𝑐)(𝑎+𝑏−𝑐) = 𝑎(𝑎+𝑏−𝑐)+𝑏(𝑎+𝑏−𝑐)+𝑐(𝑎+𝑏−𝑐) = (𝒂 × 𝒂)+(𝒂 × 𝒃)−(𝒂 × 𝒄)+(𝒃 × 𝒂)+(𝒃 × 𝒃)−(𝒃 × 𝒄) + (𝒄 × 𝒂)+(𝒄 × 𝒃)−(𝒄 × 𝒄) = 𝑎^2+𝑎𝑏−𝑎𝑐+𝑏𝑎+𝑏^2−𝑏𝑐+𝑐𝑎+𝑐𝑏−𝑐^2 = 𝑎^2+𝑎𝑏−𝑎𝑐+𝑎𝑏+𝑏^2−𝑏𝑐+𝑎𝑐+𝑏𝑐−𝑐^2 = 𝑎^2+𝑏^2−𝑐^2+𝑎𝑏+𝑎𝑏−𝑏𝑐+𝑏𝑐−𝑎𝑐+𝑎𝑐 = 𝒂^𝟐+𝒃^𝟐−𝒄^𝟐+𝟐𝒂𝒃